Modern epidemiology - Rothman, Kenneth J. (Wolters Kluwer / Lippincott Williams & Wilkins ;, 2021)
The thoroughly revised and updated Third Edition of Dr. Rothman's acclaimed Modern Epidemiology reflects the conceptual development of this evolving science and the engagement of epidemiologists with an increasing range of current public health concerns.